2020
DOI: 10.3389/fonc.2020.608304
|View full text |Cite
|
Sign up to set email alerts
|

Durable Response to Sintilimab and Chidamide in a Patient With Pegaspargase- and Immunotherapy-Resistant NK/T-Cell Lymphoma: Case Report and Literature Review

Abstract: The prognosis of patients with relapsed/refractory NK/T-cell lymphoma (NKTCL) is dismal. Immunotherapy has showed encouraging anti-tumor activity in patients with asparaginase-resistant NKTCL; however, only a portion of patients benefit and the median response duration is rather short. Treatment strategies have not been identified for immunotherapy-resistant NKTCL. We describe a patient with primary cutaneous NKTCL experienced disease progression after pegaspargase-based chemotherapy and PD-1 inhibitor (sintil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Moreover, HDAC inhibitors are now increasingly being used in combination with other types of anticancer drugs for the treatment of various malignancies. Chidamide is an innovative drug independently developed in China, which can exert anti-tumor activity by reversing tumor cell resistance, increasing tumor cell chemosensitivity, potently regulating immunity and potential direct anti-tumor effects[ 7 , 8 ]. In December 2014, chidamide was approved by China Food and Drug Administration for the treatment of relapsed or refractory peripheral T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HDAC inhibitors are now increasingly being used in combination with other types of anticancer drugs for the treatment of various malignancies. Chidamide is an innovative drug independently developed in China, which can exert anti-tumor activity by reversing tumor cell resistance, increasing tumor cell chemosensitivity, potently regulating immunity and potential direct anti-tumor effects[ 7 , 8 ]. In December 2014, chidamide was approved by China Food and Drug Administration for the treatment of relapsed or refractory peripheral T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chidamide could increase PD-L1 expression in the tumor microenvironment, and preclinical studies have demonstrated synergy between chidamide, and PD-1 blockade in solid tumors ( 55 , 57 ). A single-arm-phase II study is therefore currently ongoing to evaluate the activity of chidamide in combination with sintilimab in relapsed or refractory peripheral T-cell lymphomas ( 58 ). It is possible that chidamide administration in the context of these combination strategies could further enhance the killing of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although HDACi and PD-1 antibody have modest efficacy as a single agent, some published literature proved that PD-1 antibody and HDACi had synergistic effects in different kinds of tumor. Two case reports on NK/T cell lymphoma have reported that combined sintilimab and chidamide therapy may lead to successful outcomes ( 28 , 29 ). Moreover, a phase IB/II trial that included 38 patients with R/R extranodal NK/T cell lymphoma who were treated with sintilimab plus chidamide showed an ORR of 59.5% and a CR rate of 48.6% ( 30 ).…”
Section: Discussionmentioning
confidence: 99%